Enhancing quality midwifery care in humanitarian and fragile settings: a systematic review of interventions, support systems and enabling environments. Issue 1 (20th January 2022) - Homer, Caroline SE; Turkmani, Sabera; Wilson, Alyce N; Vogel, Joshua P; Shah, Mehr Gul; Fogstad, Helga; Langlois, Etienne V
Abstract : Introduction: Women and children bear a substantial burden of the impact of conflict and instability. The number of people living in humanitarian and fragile settings (HFS) has increased significantly over the last decade. The provision of essential maternal and newborn healthcare by midwives is crucial everywhere, especially in HFS. There is limited knowledge about the interventions, support systems and enabling environments that enhance midwifery care in these settings. The aim of this paper is to identify the factors affecting an enabling environment for midwives in HFS and to explore the availability and effectiveness of support systems for midwives. Methods: A structured systematic review was undertaken to identify peer-reviewed primary research articles published between 1995 and 2020. Results: In total, 24 papers were included from Afghanistan, Bangladesh, Nigeria, Democratic Republic of Congo, South Sudan and Sudan, Ethiopia, Pakistan, Uganda and Liberia. There were two broad themes: (1) the facilitators of, and barriers to, an enabling environment, and (2) the importance of effective support systems for midwives. Facilitators were: community involvement and engagement and an adequate salary, incentives or benefits. Barriers included: security and safety concerns, culture and gender norms and a lack of infrastructure and supplies. Support systems were: education, professional development, supportive supervision, mentorship and workforce planning. Conclusion: More efforts are needed to develop and implement quality midwifery services in HFS. There is an urgent need for more action and financing to ensure better outcomes and experiences for all women, girls and families living in these settings. PROSPERO registration number: CRD42021226323.